Anti-LGI1 encephalitis: Clinical syndrome and long-term follow-up. (4th October 2016) - van Sonderen, Agnes; Thijs, Roland D.; Coenders, Elias C.; Jiskoot, Lize C.; Sanchez, Esther; de Bruijn, Marienke A.A.M.; van Coevorden-Hameete, Marleen H.; Wirtz, Paul W.; Schreurs, Marco W.J.; Sillevis Smitt, Peter A.E.; Titulaer, Maarten J.
Abstract : Objective: This nationwide study gives a detailed description of the clinical features and long-term outcome of anti–leucine-rich glioma-inactivated 1 (LGI1) encephalitis. Methods: We collected patients prospectively from October 2013, and retrospectively from samples sent to our laboratory from January 2007. LGI1 antibodies were confirmed with both cell-based assay and immunohistochemistry. Clinical information was obtained in interviews with patients and their relatives and from medical records. Initial MRI and follow-up MRI were revised blindly. Neuropsychological assessment was performed in those patients with follow-up over 2 years. Results: Annual incidence in the Netherlands was 0.83/million. A total of 34/38 patients had a limbic encephalitis. Subtle focal seizures (66%, autonomic or dyscognitive) and faciobrachial dystonic seizures (FBDS, 47%) mostly occurred before onset of memory disturbance. Later in the disease course, 63% had tonic-clonic seizures. Initial MRI showed hippocampal T2 hyperintensity in 74% of the patients. These lesions evolved regularly into mesial temporal sclerosis (44%). Substantial response to immunotherapy was seen in 80%, with early response of seizures and slow recovery of cognition. At follow-up ≥2 years, most surviving patients reported mild residual cognitive deficit with spatial disorientation. A total of 86% had persistent amnesia for the disease period. Relapses were common (35%) and presented up to 8 years after initial disease. Two-year case fatality rate was 19%. Conclusions: Anti-LGI1 encephalitis is a homogenous clinical syndrome, showing early FBDS and other focal seizures with subtle clinical manifestations, followed by memory disturbances. Better recognition will lead to earlier diagnosis, essential for prompt start of treatment. Long-term outcome of surviving patients is mostly favorable, but relapses are common.